Reinforcement of Pancasila Student Profile Through Religious Activities at Al-Islam Modern Islamic Boarding School, Nganjuk - Ubaidillah, Muh. Hafidh (J-PAI: Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine the role of religious activities in strengthening the character of students summarized in the Pancasila Student Profile. The method used is descriptive qualitative with the type of field research. Observation, interviews, document analysis, and documentation were used to collect data during the research. This study has concluded that Al-Islam Modern Islamic Boarding School offers a diverse range of activities imbued with religious values. The activities in question are as follows: fardu prayers in congregation, sorogan Al-Quran, reading Al-Quran, Duha prayers in congregation, recitation of kitab kuning (turath), KBM (teaching and learning activities), takror (repeated learning), Muhadlarah, scouts, Roan (mass cleaning), tahlil reading, Maulid Barzanji, pilgrimage to the grave of the founder of Pesantren, various competitions, PHBI (Commemoration of Islamic Holidays), hiking, wade game, and holy journey. The findings of research indicate that religious activities at Al-Islam Modern Islamic Boarding School contribute to the strengthening of the Pancasila Student Profile of the students. This can be observed in various aspects of the Pancasila Student Profile, as illustrated by these religious activities, including faith, fear of God Almighty, noble character, and cooperation. The dimensions of faith and morals towards nature become more robust as a result of these activities, while the cooperation dimension is reinforced through collaboration and a sense of caring.